Perbandingan Keterampilan Passing Bawah Permainan Bola Voli Dengan Menggunakan Bola Sesungguhnya Dan Modifikasi Bola Plastik Pada Siswa Kelas X SMK Negeri 5 Halmahera Barat - Ismail, Isnardi; Nuryastuti, Triana; Tinamba, Safri (Peneliti.net, 2025)
This study aims to compare underhand passing skills in volleyball using a real ball and a modified plastic ball. The benefits of this study are for physical education teachers in developing learning innovations using modified plastic balls to improve underhand passing skills in volleyball. It is hoped that this will help students improve their ability to perform underhand passing skills better. This study is a comparative study using a survey method. Data collection used an underhand passing test using a real volleyball and a modified plastic ball. This study was conducted on 10th-grade students of SMK Negeri 5 West Halmahera. The population was all 73 students of SMK Negeri 5 West Halmahera, with a sample size of 12 students. The variable in this study was a single variable, namely underhand passing skills of SMK Negeri 5 West Halmahera students. In this study, differences between male and female students were not considered. The analysis technique used was the t-test.The results of this study can be concluded that the skill of passing under volleyball using a modified plastic ball is more effective or makes it easier for class X students of SMK Negeri 5 West Halmahera to master the basic technical skills of passing under. This can be shown from the results of the hypothesis test that between the total score (%) of passing under using a real volleyball and the total score (%) of passing onions using a modified plastic ball. From the test results, the t-count price was obtained at -5.28, while from the t-table it was obtained at 2.10 (attached data). It turns out that the t-count price is smaller than the t-table, or the t-count price is outside the Ho acceptance area so it can be concluded that H0 is rejected and H1 is accepted.